Editorial - Hakan Akin (Cumhuriyet University, 2013)
Dear Colleagues,   We are pleased that the January 2013 issue of the Cumhuriyet Dental Journal was published. Thank you very much to all authors and reviewers for their contributions. Thus, become a widely distributed journal worldwide; please cite CDJ in your papers.   Hope to meet in the next issue.   Assoc. Prof. Dr. Hakan Akin Editor-in-Chief Cumhuriyet Dental Journal